A feasibility study of an in-the-wild experimental public access WiFi network - Sathiaseelan, Arjuna; Mortier, Richard; Goulden, Murray; Greiffenhagen, Christian; Radenkovic, Milena; Crowcroft, Jon; McAuley, Derek (2014)
Universal Internet access has become critical to modern life, leading to many explorations of approaches to increase its availability. In this paper we report on a study of one such approach, PAWS, that seeks to understand the technical and social constraints of providing Internet access, free at the point of use, by sharing existing broadband subscribers' connections. We elaborate the technical and social context of our deployment, a deprived neighbourhood in a medium-sized British city, and discuss the constraints on and resulting architecture of this system, including the authentication and security mechanisms necessary for a service of this kind. We then report on the use of our deployment over a period of seven months from July 2013 to February 2014, including analyses of the performance and usage of the network. Our data show that PAWS is socially and technically feasible and has the potential to provide Internet access economically to many who are currently digitally disenfranchised. However, doing so requires overcoming numerous challenges, both technical and social